Review of Aboriginal child health services in remote Western Australia identifies challenges and informs solutions - Philippa J Dossetor; Kathryn Thorburn; June Oscar; Maureen Carter; James Fitzpatrick; Carol Bower; John Boulton; Emily Fitzpatrick; Jane Latimer; Elizabeth J Elliott; Alexandra LC Martiniuk (BMC, 2019)
Abstract Background Despite a national focus on closing the gap between Aboriginal and non-Aboriginal child health outcomes in Australia, there remain significant challenges, including provision of health services in very remote communities. We aimed to identify and map child health services in the very remote Fitzroy Valley, West Kimberley, and document barriers to effective service delivery. Methods Identification and review of all regional child health services and staffing in 2013. Verification of data by interview with senior managers and staff of key providers in the Western Australian Country Health Service, Kimberley Population Health Unit, Nindilingarri Cultural Health Services and non-government providers. Results We identified no document providing a comprehensive overview of child health services in the Fitzroy Valley. There were inadequate numbers of health professionals, facilities and accommodation; high staff turnover; and limited capacity and experience of local health professionals. Funding and administrative arrangements were complex and services poorly coordinated and sometimes duplicated. The large geographic area, distances, extreme climate and lack of public and private transport challenge service delivery. The need to attend to acute illness acts to deprioritise crucial primary and preventative health care and capacity for dealing with chronic, complex disorders. Some services lack cultural safety and there is a critical shortage of Aboriginal Health Workers (AHW). Conclusions Services are fragmented and variable and would benefit from a coordinated approach between government, community-controlled agencies, health and education sectors. A unifying model of care with emphasis on capacity-building in Aboriginal community members and training and support for AHW and other health professionals is required but must be developed in consultation with communities. Innovative diagnostic and care models are needed to address these challenges, which are applicable to many remote Australian settings outside the Fitzroy Valley, as well as other countries globally. Our results will inform future health service planning and strategies to attract and retain health professionals to work in these demanding settings. A prospective audit of child health services is now needed to inform improved planning of child health services with a focus on identifying service gaps and training needs and better coordinating existing services to improve efficiency and potentially also efficacy.